Efektivitas Aplikasi PEKA Online Sebagai Media Pendukung Terciptanya Kerja Aman di PT. PGE Area Lumut Balai - Tiara oktafiani; Muhammad Nasir; Hadi Syaputra; Rasmila (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
This study discusses the effectiveness of the PEKA Online application as a Supporting Media for the Creation of Safe Work at PT. PGE Lumut Balai Area. This study aims to determine the success of the application of PEKA Online as a Supporting Media for the Creation of a Safe Work Environment. Efforts to prevent work accidents have been carried out by participating in several OSH trainings, but there is still no awareness of workers about the importance of working safely in a work environment. Problems at PT. PGE Lumut Balai Area in the form of unsafe worker behavior such as lack of information and skills so that they fail to implement interventions, safeguard the work environment, and identify hazards. The use of PEKA Online as one of the official work accident prevention efforts will be carried out in 2021. This research was conducted using descriptive qualitative and quantitative approaches. Data was collected through interviewing resource persons, filling out questionnaires, observing the work environment, and documenting the PEKA Online application. The theory used in this study uses the D&M information system success model created by De Lone and Mc Lean. This study uses six indicators of success, namely system quality, information quality, service quality, intensity of application use, user satisfaction and net benefits. The collection of research data samples was carried out by distributing 62 questionnaires to PEKA Online application users who work at PT. PGE Lumut Balai Area. Determination of the number of samples using the Slovin method so that the number of samples of PEKA Online application users is 160. The results of this study indicate that the use of the PEKA Online application is effective as a Supporting Media for the Creation of Safe Work. This is based on the results of the analysis of system quality indicators which have an effectiveness of 74.19%. The results of the analysis of the information quality indicator stated that the percentage of answers was 79.09%. The service quality indicator has an effectiveness percentage of 77.35%. The indicator of the intensity of using the application from the processed data results in an effectiveness percentage of 81.29%. The user satisfaction indicator gets an effectiveness value of 78.27%. And regarding the net benefits get a percentage value of 76.85%.